(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The plot of Hayavadana longs for the sixth story in Vetala Panchavinshati, a constituent of Somadeva’s Kathasaritsagara. There, a beautiful woman is married to a washer man. One day, a couple and the better half’s brother participated in a festival at Kali’s temple. The husband sacrifices his head to the Deity, followed by the sacrifice of the better half’s brother. When the woman prepares to offer her head, the goddess not only impedes her but also helps her by reviving the dead. But the woman mixes up the heads. The head of the husband is on the brother’s shoulders and vice versa. The moral dilemma is: who is her husband? The Vikrama solves this problem by deciding that the figure with the husband’s head is the actual husband of the woman. He holds that this is the head that determines the recognition of a person.